Hegel's Introduction to the System : Encyclopaedia Phenomenology and Psychology - Hegel, Georg Wilhelm Friedrich, 1770-1831 (Book collections on Project MUSE., 2014)
The book includes a fresh translation of "Phenomenology" and "Psychology," an extensive section-by-section commentary, and a sketch of the system to which this work is an introduction